Inflation, the Payments Period and the Demand for Money - Barro, Robert J. (Journal of Finance, 1971)
Part I of this paper develops a model of economic response to inflation. Sections A, B, and C consider the maximizing behavior of employers and employees in the context of a steady rate of inflation. Since the rate of price change can be translated into an effective cost of holding money, a higher rate provides increased incentive for economizing on cash balances. Two methods of economizing are considered: first, (Sections A and B), reductions of the time interval between various types of payments (increases in and, second (Section C), decreases in the fraction of transactions. With a given fraction of monetized transactions, the selection of the optimal length of time between (wage and other types of) payments involves a tradeoff of the inventory type. Given some fixed (real) cost of making payments, a higher rate of price change reduces the optimalpayment interval (increases velocity) and produces a corresponding reduction in average real holdings. The demand-for-money function which is implied by optimal-payments period selection approaches an inflation-rate elasticity of 1/2 as the rate of inflation becomes large (relative to real rates of return in the economy). However, this formulation assumes that the fraction of monetized transactions is unaffected by changes in the inflation rate. In fact, money may be viewed as a medium which provides certain transactions benefits (in terms of physical convenience, general acceptability, et cetera) in comparison with alternative media. At a higher rate of price change, the cost of retaining as a payments medium is increased (relative to